TESTING THE RELATIONSHIPS SUSTAINABLE COMPETITIVE ADVANTAGE - Iqbal Arraniri; Eldes Willy Filatrovi; Pramudi Harsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze the relationships between knowledge diversity, knowledge creation, innovativeness, and sustainable competitive advantage. The respondents of this study were 200 employees from SMEs in Central Java - Indonesia. Data were obtained using the distribution of questionnaires and analyzed by applying structural equation modeling (SEM) with AMOS 20 software. The results revealed that knowledge diversity and knowledge creation had a relation with innovativeness and sustainable competitive advantage. Keywords: knowledge diversity, knowledge creation, innovativeness, sustainable competitive advantage